Affinity purification of metalloprotease from marine bacterium using immobilized metal affinity chromatography. Issue 11 (9th June 2016) - Li, Shangyong; Wang, Linna; Yang, Juan; Bao, Jing; Liu, Junzhong; Lin, Shengxiang; Hao, Jianhua; Sun, Mi
Abstract : In this study, an efficient affinity purification protocol for an alkaline metalloprotease from marine bacterium was developed using immobilized metal affinity chromatography. After screening and optimization of the affinity ligands and spacer arm lengths, Cu‐iminmodiacetic acid was chosen as the optimal affinity ligand, which was coupled to Sepharose 6B via a 14‐atom spacer arm. The absorption analysis of this medium revealed a desorption constant K d of 21.5 μg/mL and a theoretical maximum absorption Q max of 24.9 mg/g. Thanks to this affinity medium, the enzyme could be purified by only one affinity purification step with a purity of approximately 95% pure when analyzed by high‐performance liquid chromatography and reducing sodium dodecyl sulfate polyacrylamide gel electrophoresis. The recovery of the protease activity reached 74.6%, which is much higher than the value obtained by traditional protocols (8.9%). These results contribute to the industrial purifications and contribute a significant reference for the purification of other metalloproteases.